Globalization of Information—Take TiKTok as an Example (Asian Journal of Social Science Studies, 2022)
Globalization is manifested in such dimensions as political globalization, economic globalization, scientific and technological globalization, and cultural globalization. Globalization of different dimensions supports and integrates. The “hardware” of information globalization is mainly concentrated in Internet and mobile communication, with obvious scientific and technological attributes. The “software” of information globalization is mainly reflected in the interaction and close connection with politics, culture, society, and other fields, with obvious communication attributes. It is a global complex integrating many elements. Information globalization brings convenience and risks to citizens at the same time. This article will take TikTok as an example to analyze the advantages and disadvantages of information globalization.